2016
DOI: 10.1515/sab-2016-0010
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Quality of Native and Frozenthawed Semen in Relation to Two Collections Performed in a 24-hour Interval and Adition of Clarified Egg Yolk to Extender

Abstract: The aim of the study was to evaluate the effect of repeated semen collection and the substitution of normal egg yolk with clarified egg yolk to commercially produced semen extender on qualitative parameters of frozen-thawed canine semen. Two semen collections were scheduled in a 24-hour interval and in each of six dogs, three 1st and three 2nd collections were performed. The frozen-thawed sperm samples were prepared either with clarified or normal egg yolk and motility and viability were evaluated. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…It is meaningful to also evaluate CASA kinematic parameters when the effect of different types of extenders on sperm quality needs to be evaluated objectively (Folkova et al 2016). In the ejaculates from the Old Kladruber stallions, the VAP, VCL, and VSL significantly differed between chosen extenders immediately after dilution.…”
Section: Discussionmentioning
confidence: 99%
“…It is meaningful to also evaluate CASA kinematic parameters when the effect of different types of extenders on sperm quality needs to be evaluated objectively (Folkova et al 2016). In the ejaculates from the Old Kladruber stallions, the VAP, VCL, and VSL significantly differed between chosen extenders immediately after dilution.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, total sperm counts were highest in the ejaculates acquired on day 1 and decreased gradually on successive days of the experiment. Folková et al (2016) also observed a decrease in sperm concentration in ejaculates obtained at 24-h intervals from dogs after three months of sexual rest. The cited authors attributed these findings to the depletion of extragonadal sperm reserves in the epididymis and vasa deferentia (Root-Kustritz 2007).…”
Section: Discussionmentioning
confidence: 71%
“…Research has shown that ejaculates collected from dogs after a long period of sexual abstinence can contain a large number of dead spermatozoa, and spermatozoa with abnormal morphology and decreased motility (Feldman and Nelson 2004). For example, Folková et al (2016) noted that the percentage of motile and viable spermatozoa was lower in ejaculates obtained after three months of sexual abstinence than in ejaculates sampled after another 24 hours. However, Taha et al (1983) found that that ejaculates collected after six weeks of sexual abstinence were characterized by normal quality parameters.…”
Section: Introductionmentioning
confidence: 99%